Quantitative sensory testing in feline osteoarthritic pain – a systematic review and meta-analysis. Issue 7 (July 2020) - Monteiro, B.P.; Otis, C.; del Castillo, J.R.E.; Nitulescu, R.; Brown, K.; Arendt-Nielsen, L.; Troncy, E.
Summary: Quantitative sensory testing (QST) is a psychophysical test used to quantify somatosensory sensation under normal or pathological conditions including osteoarthritis (OA). Objective: This study aimed to conduct a systematic review and meta-analysis of studies using QST in healthy and osteoarthritic cats, registered at Systematic Review Research Facility (#26-06-2017). Design: Hierarchical models with random intercepts for each individual study extracted through the systematic review were fit to subject-level data; QST measures were contrasted between healthy and osteoarthritic cats. Four bibliographic databases were searched; quality and risk of bias assessment were performed using pre-established criteria. Results: Six articles were included; most were of high quality and low risk of bias. Punctate tactile threshold ( n = 70) and mechanical temporal summation ( n = 35) were eligible for analysis. Cats with OA have lower punctate tactile threshold [mean difference (95%HDI): −44 (−60; −26) grams] and facilitated temporal summation of pain [hazard ratio (95%HDI): 5.32 (2.19; 14) times] when compared with healthy cats. The effect of sex and body weight on sensory sensitivity remained inconclusive throughout all analyses. Due to the correlation between age and OA status, it remains difficult to assess the effect of OA on sensory sensitivity, independently of age. Conclusions: Clear and transparent reporting using guidelines are warranted. Similar to people, centralized sensitization is a feature of OA in cats. Future studies should try to elucidate the age effect on feline OA. Research with natural OA in cats is promising with potential to benefit feline health and welfare, and improve translatability to clinical research.